Ambulatory Surgery vs Overnight Observation for Total Thyroidectomy: Cost Analysis and Outcomes. Issue 1 (March 2021) - Rosen, Philip; Bailey, Luke; Manickavel, Sudhir; Gentile, Christopher; Grayson, Jessica; Buczek, Erin
Objective: To compare financial impact between patients undergoing ambulatory (same-day discharge) vs overnight admission after total thyroidectomy while showing associated surgical outcomes. Study Design: Retrospective review. Setting: University of Alabama at Birmingham Medical Center from October 2011 and July 2017. Methods: Patients undergoing total thyroidectomy without concurrent procedures were selected for review. Demographics, comorbidities, admission status, postoperative outcomes including minor and major complications, charges, and costs were collected. Admission status was categorized as inpatient (admission to hospital ≥1 night) or outpatient (discharged from the postoperative recovery unit). Costs were obtained from all related hospital, clinic, and emergency department visits at the University of Alabama at Birmingham within 30 days of the original surgery. After statistical analysis, outcomes and costs were compared between inpatient and outpatient total thyroidectomy patients. Results: Of 870 total thyroidectomy patients included for analysis, 367 (42.2%) met outpatient criteria. A total of 169 patients (19.4%) had a complication, and only hypocalcemia occurred significantly more in the inpatient group (14.3% vs 9.26%; P < .05). No complications occurred more frequently in the outpatient population. There were no mortalities. There was a statistically significant difference between the total cost of inpatient and outpatient thyroidectomies, with outpatient surgery costing on average $2367.27 less per patient ( P < .0001). Conclusion: Outpatient total thyroidectomy can lead to cost reduction in highly selected patients who have few comorbidities while remaining safe for the patient.